Relationships among airport service quality, satisfaction, and behavioral intentions : an application on Lisbon Airport - Salvador, Bárbara Morgado (2019)
By exceeding the 25 million passengers in a year, Lisbon airport entered the ranking of the biggest European airports in 2017. This fact raises new concerns regarding service quality and passengers’ experience. As such, the purpose of this research is to extend the notions of service quality and satisfaction in the context of airport industry taking into account passengers’ behavioral intentions. In the context of an explanatory study, an online questionnaire was conducted. There were obtained 398 valid answers from passengers who travelled at least once during the last 12 months through the Lisbon airport. A path analysis was conducted to examine the model linking service quality, passenger satisfaction and behavioral outcomes, while a multivariate analysis determined the effects of a number of sociodemographic and travel characteristics on behavioral intentions - word-of-mouth and revisit intentions. Results showed that the impact of airport service quality on behavioral intentions is mediate by passengers’ satisfaction. The efficiency and effectiveness of the airport service are the factors that most affect passenger’ satisfaction, and this one has a high positive effect on word-of-mouth intentions. Moreover, there were found relevant differences on behavioral intentions according to passengers’ origin country and travel frequency. Findings that contribute to existent academic literature on airport industry but have also practical implication for managers of the Lisbon airport are discussed, limitations of the study are noted and possible areas for future research are indicated.